Physical activity and quality of life of hypertensive patients with and without diabetes: a cross-sectional study - Khaw, Wan Fei; Syed Hassan, Syed Tajuddin; Abdul Latiff, Latiffah (Community Health Society Malaysia, 2017)
Background: Physical activity is associated with health-related quality of life in general population with and without chronic conditions, but little is known, whether and how, this relationship exists in hypertensive and diabetes patients, especially in Malaysia. Thus, this cross-sectional study was primarily to determine if and how physical activity was related to hypertensive patients with and without diabetes. Materials and Methods: The sample consisted of 260 hypertensive patients receiving treatment in Hospital Serdang, Selangor, Malaysia. Participants completed measures of physical activity and quality of life questionnaires. The multiple analysis of covariance was used to examine the effects of physical activity on the quality of life scores. Result: Subjects were divided into physically active group (n=139) and a physically inactive group (n=121). Of these, 40% were diagnosed without diabetes mellitus and 60% were patients with diabetes. Respondents in the hypertension with diabetes group were older, had lower educational level, and more were unemployed than those hypertensive without diabetes. The quality of life scores were significantly different comparing physically active and inactive subjects. The presence of diabetes contributed to higher differences in quality of life scores. Higher physical activity was positively associated with higher quality of life measures in both physical and mental domains. Conclusion: Higher levels of physical activity may improve quality of life in both hypertensive patients with and without diabetes. Therefore, incorporating more physical activities into the lifestyle of hypertensive patients, may improve their quality of life and prevent complications.